2019
DOI: 10.1007/s10157-019-01747-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of HNF1B-related disorders in a Japanese population

Abstract: Background Hepatocyte nuclear factor 1β (HNF1B), located on chromosome 17q12, causes renal cysts and diabetes syndrome (RCAD). Moreover, various phenotypes related to congenital anomalies of the kidney and urinary tract (CAKUT) or Bartter-like electrolyte abnormalities can be caused by HNF1B variants. In addition, 17q12 deletion syndrome presents with multi-system disorders, as well as RCAD. As HNF1B mutations are associated with different phenotypes and genotype-phenotype relationships remain unclear, here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 23 publications
5
40
0
2
Order By: Relevance
“…In our study, six of the 14 patients (43%) had entire gene deletion. Similar to many other studies, all four missense mutations detected in our study were located in the DNA binding domain of the HNF1β protein [ 3 , 5 , 7 , 22 ]. HNF1B mutations are inherited in an autosomal dominant pattern and equally affect both sexes [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, six of the 14 patients (43%) had entire gene deletion. Similar to many other studies, all four missense mutations detected in our study were located in the DNA binding domain of the HNF1β protein [ 3 , 5 , 7 , 22 ]. HNF1B mutations are inherited in an autosomal dominant pattern and equally affect both sexes [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…The phenotypes of HNF1B mutations are extremely variable with inter- and intrafamilial variability, and patients with HNF1B mutations typically present CAKUT, either isolated or in combination with extrarenal manifestations [ 5 , 6 , 13 , 14 ]. Cystic disease, including cystic dysplasia, is by far the most commonly identified renal phenotype in both pediatric and adult populations in most large-scale studies [ 7 , 8 , 10 , 24 ], and our study corroborated this finding (bilateral multiple renal cysts in seven patients (50%) and unilateral renal cysts with contralateral multicystic dysplastic kidney or vesicoureteral reflux in five patients (36%).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This condition has also been associated with hypomagnesemia . Recently, Nagano et al reported that patients with HNF1B ‐related nephropathy can have hypokalemia and hypomagnesemia . Bech et al conducted a thiazide loading test on cases with HNF1B ‐related nephropathy.…”
Section: Pseudo‐bs/gsmentioning
confidence: 99%